Language, Culture, and Ethnography of Communication - Amrullah; Habiburrahman; Satriawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Language reflects the realities of human life activities. As social beings, humans require communication, which functions effectively when facilitated by language. Therefore, language influences human thought patterns. Polite language, a hallmark of Indonesian culture, has been passed down through generations, underscoring the close relationship between language and culture. Effective language expression is also supported by good literacy understanding. This study aims to explain language use in society through the Ethnography of Communication approach, emphasizing the importance of context in interpreting speech and its functions. Linguists have traditionally found it easy to explain sentences from grammatical and semantic perspectives but often struggle with the intention and functional use of speech. Ethnography of Communication seeks to address this gap by incorporating aspects of speech or communication, thus making linguistic components more comprehensive. The research method used was a literature study, with library materials serving as the primary data source. The findings indicate that language was structured according to patterns, not randomly, but within subsystems such as phonology, morphology, syntax, and semantics. These patterns correspond to the needs and functions of each societal group. Ethnography of Communication examines the communication patterns of a community or cultural society, highlighting the role of language in the communicative behaviour of a society and how language was used within different cultures.